2008
DOI: 10.1002/jhm.319
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking among health care workers at King Hussein Medical Center

Abstract: OBJECTIVE:The purpose of the study was to investigate the prevalence of smoking among health care workers (HCWs) at King Hussein Medical Center (KHMC), the biggest tertiary-care center in Jordan.METHODS: Data were collected using a self-reported questionnaire on cigarette smoking distributed among 760 HCWs. Questions were designed to collect various demographic parameters and different aspects related to cigarette smoking. RESULTS:Six hundred HCWs returned the completed questionnaire. Responders were divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
12
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 11 publications
7
12
0
1
Order By: Relevance
“…Smoking habit was significantly higher among men than women. These findings are consistent with other studies on healthcare professionals and the general population in Jordan (7,15,16). These results were expected as the reported smoking prevalence rate in developing countries was also higher in men than women, and because smoking among women is not generally accepted culturally by the Jordanian population (18).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Smoking habit was significantly higher among men than women. These findings are consistent with other studies on healthcare professionals and the general population in Jordan (7,15,16). These results were expected as the reported smoking prevalence rate in developing countries was also higher in men than women, and because smoking among women is not generally accepted culturally by the Jordanian population (18).…”
Section: Discussionsupporting
confidence: 91%
“…This was lower than the prevalence rate of smoking (65%) among healthcare workers at the biggest tertiary hospital in Jordan (15), and lower than the prevalence rate of smoking (38.8%) among healthcare professionals working at other hospitals (16). This suggests that healthcare professionals at primary healthcare centres may hold a more positive attitude toward smoking habits compared to those working at hospitals.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Despite this fact, the prevalence of smoking among male Jordanian nurses is still surprisingly the highest in comparison with other nurses around the world. The smoking rate among Jordanian male nurses was three times higher than the smoking rate among female nurses --49% and 17% respectively 2 . Another study conducted by Shishani, Nawafleh, and Froelicher 3 showed that the smoking rate among general Jordanian nurses was 41.5% and significantly more male nurses smoked more than female nurses.…”
Section: Introductionmentioning
confidence: 77%